The demotivational factors in German learners of Chinese - Cao, Qingyang (2015)
Studies on L2 demotivation find out that the major factors demotivate English language learners and other foreign language learners (e.g Arabic learners) in the learning process include teacher-related factors, course contents and materials, negative attitude toward the L2, reduced self-confidence and lack of practicing opportunities. Based on the findings of previous studies, this research paper aims to find out what factors demotivate German learners of Chinese language. Semi-structured interview is employed to find out what demotivate the learners and a questionnaire is used to investigate which factors are more salient than others. The study result shows that the difficulty of Chinese language and lack of time are rated as the most salient demotives, followed by reduced self-confidence, boring teaching style and unsatisfactory course contents and materials, lack of practicing opportunities, lack of learning goals and teacher incompetence. What’s noteworthy is that teacher incompetence is identified as one of the primary L2 demotives in previous studies, yet it is ranked at the bottom of the list of demotives in this study.